A refined management system focusing on medication dispensing errors: A 14-year retrospective study of a hospital outpatient pharmacy - Yangyang Gao; Yi Guo; Minglin Zheng; Lulu He; Mengran Guo; Zhaohui Jin; Ping Fan (Elsevier, 2023)
Objectives: This study aimed to evaluate the efficiency of a 14-year refined management system for the reduction of dispensing errors in a large-scale hospital outpatient pharmacy and to determine the effects of person-related and environment-related factors on the occurrence of dispensing errors. Methods: A retrospective study was performed. Data on dispensing errors, inventory and account management from 2008 to 2021 were collected from the electronic system and evaluated using the direct observation method and the Plan-Do-Check-Act (PDCA) cycle. Results: The consistency of the inventory and accounts increased substantially (from 86.93 % to 99.75 %) with the implementation of the refined management program. From 2008 to 2021, the total number of dispensing errors was reduced by approximately 96.1 %. The number of dispensing errors in quantity and name was reduced by approximately 98.2 % and 95.07 %, respectively. A remarkable reduction in the error rate was achieved (from 0.014 % to 0.00002 %), and the rate of dispensing errors was significantly reduced (0.019 % vs. 0.0003 %, p < 0.001). Across all medication dispensing errors, human-related errors decreased substantially (208 vs. 7, p < 0.05), as did non-human-related errors also (202 vs. 9, p < 0.05). There was a correlation between the occurrence of errors and pharmacists' sex (females generally made fewer errors than males), age (more errors were made by those aged 31-40 years), and working years (more errors were made by those with more than 11 years of work experience) from 2016 to 2021. The technicians improved during this procedure. Conclusions: Refined management using the PDCA cycle was helpful in preventing dispensing errors and improving medication safety for patients.